2020
DOI: 10.1080/22221751.2020.1823890
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 neutralizing antibody responses are more robust in patients with severe disease

Abstract: We studied plasma antibody responses of 35 patients about 1 month after SARS-CoV-2 infection. Titers of antibodies binding to the viral nucleocapsid and spike proteins were significantly higher in patients with severe disease. Likewise, mean antibody neutralization titers against SARS-CoV-2 pseudovirus and live virus were higher in the sicker patients, by ∼5-fold and ∼7-fold, respectively. These findings have important implications for those pursuing plasma therapy, isolation of neutralizing monoclonal antibod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
117
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 12 publications
15
117
1
4
Order By: Relevance
“…Previous observations suggested that an IgG upsurge for SARS-CoV correlates with a clinical worsening of pneumonia (5). In a pre-print study, SARS-Cov2 neutralizing Ab responses result more robust in 35 patients with severe disease, about 1 month after infection (13). Moreover, in five patients with severe Covid-19, three potent neutralizing antibodies against multiple epitopes on the SARS-Cov2 spike have been detected: one anti-RBD, one other anti-NTD (N-terminal domain) and a third able to bind two separate RBD (9).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous observations suggested that an IgG upsurge for SARS-CoV correlates with a clinical worsening of pneumonia (5). In a pre-print study, SARS-Cov2 neutralizing Ab responses result more robust in 35 patients with severe disease, about 1 month after infection (13). Moreover, in five patients with severe Covid-19, three potent neutralizing antibodies against multiple epitopes on the SARS-Cov2 spike have been detected: one anti-RBD, one other anti-NTD (N-terminal domain) and a third able to bind two separate RBD (9).…”
Section: Discussionmentioning
confidence: 88%
“…f. Therapeutic use of serum Abs from healed subjects (plasma therapy) might have positive effects: recent unofficial data would indicate that a therapy with hyper-immune sera in the initial covid-19 appears to prevent the disease progression, while for patients in advanced severe disease a significant improvement has been noted. This could indicate that Abs might have a favorable effect, but, presumably, only if in high quantities (13), as it occurs in hyper-immune sera therapy. In effect, besides a direct neutralization of viral activities, such as replication, that reduces the viral titer, high Ab amounts might also act leading the Ag/Ab rate closer to the equivalence, that reduce or avoid formation of soluble and fixed ICs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and demographic correlates of the neutralising antibody response are described in Table 3. Neutralising antibody responses correlated with disease severity in all studies in which this association was tested [7,43,49,108,117,126,127,[135][136][137]. Importantly, the few studies that investigated asymptomatic cases found those individuals were considerably less likely to develop detectable serum neutralising antibody responses than cases with symptoms.…”
Section: Protective Immunitymentioning
confidence: 97%
“…Antibody titre • Ten studies reported a higher titre of neutralising antibodies in more clinically severe cases [7,43,49,108,126,127,[134][135][136][137]. • One study reported undetectable neutralising activity in plasma from a majority of asymptomatic cases [126].…”
Section: Clinical Disease Severitymentioning
confidence: 99%
“…Wang et al further reported that mean antibody neutralization titers against SARS-CoV-2 live virus were ~ sevenfold higher in the sicker patients and that patients with severe COVID-19 had more robust binding antibodies to both the N protein and S trimer (Wang P et al 2020 ). Even though antibodies against the SARS-CoV-2 N protein do not provide protective immunity against infection (Gralinski and Menachery 2020 ), specific antibodies against the S protein do (Gao et al 2020 ).…”
Section: Serological Characteristics Of Covid-19 Patientsmentioning
confidence: 99%